2023
DOI: 10.18502/jimc.v6i3.12859
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Static Balance Differences between Adolescents with Idiopathic Scoliosis and Healthy Age-matched Adolescents: A Cross-sectional Study

Abstract: Background: The aim of this study was to compare postural control between Adolescents with Idiopathic Scoliosis (AIS) and healthy adolescents. Methods: In this cross-sectional study, 20 AIS adolescents with a right thoracic curvature between 10 and 45 degrees and 20 healthy adolescents were matched to compare postural control. Postural control assessments included Center of Pressure (COP) range and COP velocity in the Anteroposterior (AP) and Mediolateral (ML) directions, and the COP sway area in the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…A review of studies on postural stability in children/adolescents with scoliosis in comparison with their typically developing peers revealed that the results were not fully consistent. Notably, both earlier studies [ 8 , 9 , 10 ] as well as recent studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] reported significant differences in stability, while others reported a lack of differences in stability [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…A review of studies on postural stability in children/adolescents with scoliosis in comparison with their typically developing peers revealed that the results were not fully consistent. Notably, both earlier studies [ 8 , 9 , 10 ] as well as recent studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] reported significant differences in stability, while others reported a lack of differences in stability [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 97%
“…Assuming that, irrespective of the primary triggers of IS, persistent asymmetric mechanical loading relative to the spinal axis may influence scoliosis development and progression, several recent studies have focused on analyzing body weight distribution (BWD) on the basis of support (BoS) between body sides [ 4 , 5 , 6 , 7 , 8 ] and assessing postural stability in children/adolescents with scoliosis [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation